(untitled) (Journal of Pakistan Orthopaedic Association, 2020)
Osteochondroma is the most common benign chondrogenic lesion of the skeleton. Arising mostly in the long bones of the appendicular skeleton but may involve flat bones as well. Calcaneum however, is an uncommon site. True incidence is still unknown as many are asymptomatic, growing during childhood through adolescent until skeletal maturity. These are managed conservatively in majority of cases. If persists or grows during adulthood with acute onset of pain should raise suspicion of malignant transformation to a chondrosarcoma which warrants its surgical excision. We present the clinical and radiological finding of a 15-year-old male with a solitary osteochondroma (35mm x 26mm) on the inferolateral aspect of right calcaneus, followed by surgical excision. Histopathology showed no malignancy and there was no recurrence at 1 year follow up.